Preparation method of Cu2O / black phosphorus catalyst for removing antibiotics in water

By using Cu2O/black phosphorus composite catalyst, the problem of difficulty in removing antibiotics in water is solved, and the efficient photocatalytic degradation effect is achieved, which significantly improves the removal rate of antibiotics.

CN119857506AActive Publication Date: 2025-04-22DALIAN MEDICAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510093287.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-22
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove antibiotics in water, especially because the components in antibiotic wastewater are complex, which can easily cause pH fluctuations and affect biochemical effects.

Method used

Cu2O/black phosphorus (Cu2O/BP) composite catalyst is used to synthesize a Cu2O/BP catalyst with a layered structure by improving the catalyst composition and preparation method for photocatalytic degradation of antibiotics.

Benefits of technology

The efficiency of photocatalytic degradation of antibiotics is improved, especially under visible light conditions, which shows higher degradation efficiency compared with pure Cu2O and pure BP catalysts, significantly improving the removal rate of antibiotics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857506A_ABST
    Figure CN119857506A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalytic water treatment in environmental chemical industry, and discloses a preparation method of a Cu2O / black phosphorus catalyst for removing antibiotics in water, and a series of Cu2O / BP composite photocatalysts are prepared by taking Cu2O and Black Phosphoru (BP) as precursor reactants. The preparation method comprises the following steps: preparing a BP catalyst through a simple hydrothermal method, calcining Cu (NO3) 2.3 H2O and BP in different proportions to generate a composite Cu2O / BP photocatalyst, and analyzing that Cu2O is loaded on a BP layer and forms a composite structure. Under the condition of visible light, the prepared catalysts are used for degrading levofloxacin hydrochloride, and then the catalytic activity of the composite photocatalyst is observed. Results show that in Cu2O / BP photocatalysts with different loading capacities, the photocatalytic degradation effects of 3% Cu2O / BP and 4% Cu2O / BP are the best, and the degradation rate within 3 hours reaches 89% which is 2.83 times of the degradation rate of pure BP, so that the efficient composite catalyst is successfully prepared by the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental chemical catalytic water treatment, relates to generating clean gas by visible light treatment, and particularly relates to a preparation method of a Cu2O / black phosphorus catalyst for removing antibiotics in water. Background Art

[0002] For the characteristics of the composition of compound antibiotic pharmaceutical wastewater, the pollution concentration is high, and physical, biological, and advanced oxidation combined processes are usually used for treatment. However, as far as the current domestic and foreign technologies are concerned, no technology has a significant and more specific effect. Therefore, antibiotic wastewater treatment is the main focus at this stage, and oxidation treatment measures are needed to effectively treat wastewater, and the treatment effect is very obvious to protect the quality of people's living environment. Antibiotic wastewater contains intermediate metabolites, surfactants, and high concentrations of acids, alkalis, and organic solvents. For the extraction and separation procedures, due to the complex composition, it is easy to cause pH fluctuations and affect biochemical effects. At present, the more practical methods for treating water pollution mainly include photocatalysis, adsorption, membrane separation, etc. Among them, photocatalysis can use the energy of solar energy to convert it into hydrogen energy for storage, and can also be used to degrade organic wastewater, but efficiency and cost are the main factors restricting the development of photocatalysis. Therefore, it is imperative to find a substance that can efficiently and cheaply degrade antibiotics in the environment.

[0003] Black Phosphorus (BP) is a form of phosphorus in nature, and is an allotrope of the common flammable red phosphorus. The preparation of BP crystals began as early as 100 years ago. BP crystals are composed of a single layer of black phosphorus flakes. BP is a p-type semiconductor, and its light absorption range can cover the ultraviolet-visible-near infrared range, and the adjustable range has great advantages over other semiconductors. Although BP has excellent photocatalytic properties, it is easily oxidized and decomposed in oxygen-containing air, water and visible light, and its properties are unstable, so it is necessary to continue to explore and study the modification of BP, which can not only retain its original photocatalytic properties, but also improve its stability.

[0004] Copper is an element in Group 11 of the periodic table. Copper is a transition metal, a naturally abundant element with the biggest benefit of being non-toxic and widely available. At room temperature, copper has the second highest electrical and thermal conductivity of all pure metals, second only to silver, and has become a frequently used material in industrial products due to its high ductility. Cu2O is one of the most studied transition metal oxide crystals, as the electrical and optical properties of semiconductor Cu are particularly useful for solar cells and technological devices. Cu2O has p-type conductivity and is cheap to prepare, and can effectively absorb sunlight. Cu2O may be used to make solar cells due to its high absorption coefficient, and is very stable, so Cu2O has good application potential in the field of solar energy conversion and photocatalysis. It is reported that nanowire photocathodes have been developed, which is currently the most effective metal oxide material. Moreover, Cu2O can become a semiconductor film, which has great development prospects for transferring electrons. Summary of the invention

[0005] Since BP is easily oxidized and decomposed in oxygen-containing air, water and visible light and becomes ineffective, and its properties are unstable, research and exploration of modifying BP can retain its original photocatalytic properties and improve its stability. Cu2O is one of the most studied transition metal oxide crystals, and has good application potential in the fields of solar energy conversion and photocatalysis. It is the most effective metal oxide material at present. Moreover, Cu2O can become a semiconductor film, which has great development prospects for transferring electrons. The present invention combines the two to avoid each other's shortcomings and produce a highly efficient composite metal photocatalyst, and studies the effects of different concentrations of Cu2O combined with BP on the degradation and photocatalytic performance of levofloxacin hydrochloride wastewater.

[0006] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a Cu2O / BP catalyst and a preparation method having good photocatalytic properties and providing new ideas for subsequent degradation of wastewater.

[0007] The present invention mainly achieves the above-mentioned object by improving the catalyst composition and preparation method. In order to achieve this object, the present invention provides:

[0008] A Cu2O / black phosphorus catalyst for removing antibiotics from water is prepared by first synthesizing a BP nanolayer, then synthesizing Cu2O particles and finally loading BP thereon. The Cu2O material is in the form of a spherical body, and the BP is in a clear layered structure. The shape of the synthesized composite material is spherical nanoparticles embedded in the layered structure.

[0009] On the other hand, a method for preparing the above-mentioned Cu2O / black phosphorus catalyst for removing antibiotics in water is provided, comprising the following steps:

[0010] (1) Preparation of BP: 0.25-0.75 g of red phosphorus was first ground into powder using a pestle and mortar, and then 70-80 mL of ethylenediamine was added. After vigorous stirring with a magnetic stirrer for 30 min, the mixture was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and placed in a constant temperature drying oven. After heating at 165 °C for 24 h, it was quickly cooled to room temperature and the product was collected with cold water. After centrifugation, it was washed three times with ethanol to remove the residual solvent ethylenediamine. The final product was dried at 40 °C in a vacuum;

[0011] (2) Preparation of Cu2O: 0.004 mol Cu(NO3)2·3H2O was dissolved in 70-90 mL EG. After stirring for 2 h, the transparent light blue solution was transferred to a 100 mL autoclave (stainless steel autoclave), sealed and transferred to an oven, then heated to 180°C and maintained for 2 h. The final yellow product was filtered and washed with ethanol several times to remove unreacted EG, and dried in air at 40°C.

[0012] (3) Preparation of Cu2O / BP: The prepared Cu2O and BP powders were dissolved in 80 mL of EG, with 1 g of BP powder and a mass ratio of Cu2O to BP of 1%-10%. After stirring for 2 h, the transparent light blue solution was transferred to a 100 mL autoclave (stainless steel autoclave), sealed and transferred to an oven, then heated to 180 °C and maintained for 2 h. The final yellow product was filtered and washed several times with ethanol to remove unreacted EG, and dried in air at 40 °C.

[0013] On the other hand, the application of composite catalyst Cu2O / BP in photocatalytic degradation of levofloxacin hydrochloride wastewater is provided. First, 3-5mg pure Cu2O, pure BP and Cu2O / BP composite catalyst with different ratios are respectively taken and added into 100mL levofloxacin hydrochloride (10mg / L), and then adsorption-desorption equilibrium between catalyst and levofloxacin hydrochloride solution is established by stirring 60min under dark conditions. A 500w xenon lamp is vertically placed at 15cm above the solution, 4mL is sampled at regular intervals, and transferred to a centrifuge tube, by centrifugation photocatalyst. Finally, an ultraviolet-visible spectrophotometer is used to measure the absorbance at 294nm, and the variation of levofloxacin hydrochloride concentration is determined by absorbance to analyze the degradation efficiency of the photocatalyst.

[0014] Compared with the prior art, the present invention has the following advantages:

[0015] 1. The composite Cu2O / BP catalyst is composed of Cu2O particles and BP particles. The BP nanolayer is prepared first and then loaded with Cu2O.

[0016] 2. The composite Cu2O / BP catalyst has strong light adsorption ability and high electron-hole separation efficiency. The material structure is stable, the photogenerated carrier transmission is fast, and the recombination of photogenerated carriers can be effectively inhibited.

[0017] 3. Compared with pure Cu2O and BP, the composite Cu2O / BP catalyst has better visible light absorption performance and greatly improves the photocatalytic degradation of levofloxacin hydrochloride solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 (a) is a scanning electron microscope image of Cu2O of Example 1, (b) is a scanning electron microscope image of BP of Example 1, and (c) is a scanning electron microscope image of 3% Cu2O / BP;

[0019] Figure 2 The photoelectron spectra of Cu2O, BP and 3%Cu2O / BP in Example 1;

[0020] Figure 3 The infrared spectra of Cu2O, BP and 3%Cu2O / BP in Example 1;

[0021] Figure 4 The UV-visible diffuse reflectance spectra of Cu2O, BP and 3%Cu2O / BP in Example 1;

[0022] Figure 5 The fluorescence spectra of Cu2O, BP and 3%Cu2O / BP in Example 1 are shown;

[0023] Figure 6 This is a graph showing the removal rate of levofloxacin hydrochloride degraded by different catalysts under visible light irradiation in Example 1. DETAILED DESCRIPTION

[0024] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial sources.

[0025] Example 1

[0026] The preparation method of the composite Cu2O / BP catalyst is as follows:

[0027] The composite materials of BP and Cu2O with different mass ratios were prepared by changing the content of Cu2O in the mixed solution before firing while keeping the BP content unchanged. The photocatalyst thus prepared is represented as Cu2O / BP (x:y), where x:y is the mass ratio of Cu2O to BP. The Cu2O / BP composite catalysts with different mass ratios (1%, 2%, 3%, 4%, 5% and 10%) were prepared by the following method: Different masses of Cu(NO3)2·3H2O and 1g of the prepared BP powder were dissolved in 80mL EG, stirred for 2h, and the transparent light blue solution was transferred to a 100mL autoclave (stainless steel autoclave), sealed and transferred to an oven, and then heated to 180℃ and maintained for 2h. The final yellow product was filtered and washed with ethanol several times to remove unreacted EG, and dried in air at 40℃.

[0028] Example 2

[0029] 0.5g red phosphorus was first ground into powder using a pestle and mortar, and then 75mL ethylenediamine was added. After vigorous stirring with a magnetic stirrer for 30min, the mixture was transferred to a 100mL polytetrafluoroethylene-lined stainless steel autoclave and placed in a constant temperature drying oven. After heating at 165°C for 24h, it was quickly cooled to room temperature and the product was collected with cold water. After centrifugation, it was washed three times with ethanol to remove the residual solvent ethylenediamine. The final product was dried at 40°C in a vacuum; BP was finally obtained.

[0030] Example 3

[0031] 0.004 mol Cu(NO3)2·3H2O was dissolved in 80 mL EG. After stirring for 2 h, the transparent light blue solution was transferred to a 100 mL autoclave (stainless steel autoclave), sealed and transferred to an oven, then heated to 180 °C and maintained for 2 h. The final yellow product was filtered and washed with ethanol several times to remove unreacted EG, and dried in air at 40 °C. Cu2O was finally obtained.

[0032] Figure 1 The scanning electron microscope images of Cu2O, BP and 3%Cu2O / BP in Example 1 are shown; Figure 1 a, is the SEM image of BP material at 10 nm. It can be seen from Figure (a) that BP has a clear layered structure. Figure 1 b is the SEM image of Cu2O nanomaterials at 1 μm. It can be seen from the figure that Cu2O exhibits a spherical shape and is connected into a rod shape. Figure 1 As shown in (c), the structure of the Cu2O / BP composite material can be seen, and the Cu2O nanoparticles are adsorbed on the layered BP.

[0033] Figure 2This is the photoelectron spectrum of Cu2O, BP and Cu2O / BP in Example 1; it confirms the presence of Cu, O and P elements in the Cu2O / BP structure.

[0034] Figure 3 The infrared spectra of Cu2O, BP and 3%Cu2O / BP in Example 1 are shown in the figure. As shown in the figure, in the infrared spectrum of Cu2O, the -1 The peak at corresponds to the stretching vibration of the Cu-O bond. The corresponding characteristic peak can also be seen in the composite sample, confirming that Cu2O / BP is composed of Cu2O and BP.

[0035] Figure 4 The UV-visible diffuse reflectance spectra of all samples in Example 1 are shown in Figure 1. Black phosphorus has a wide range of light absorption and excellent light absorption ability. The absorption peak of Cu2O is at 400-600nm, and its light absorption ability is relatively weak. The absorption peaks of Cu2O / BP with different ratios are all in the middle of the two pure samples. Compared with Cu2O, the composite sample has a larger absorption range of visible light.

[0036] Figure 5 It is the fluorescence spectrum of all samples in Example 1; as shown in the figure, the PL intensity of Cu2O and BP is higher than that of the Cu2O / BP composite material, and the PL intensity of the Cu2O / BP composite material is reduced, which means that the presence of BP reduces the PL intensity, effectively separates the photogenerated electron-hole pairs, reduces the recombination of photogenerated electron-hole pairs, and realizes effective electron transfer.

[0037] Figure 6 The removal rate of levofloxacin hydrochloride degradation by different catalysts under visible light irradiation in Example 1; Application Example 1

[0038] First, 3-5 mg of pure Cu2O, pure BP and Cu2O / BP composite catalyst with different proportions (1%, 2%, 3%, 4%, 5% and 10%) were added to 100 mL of levofloxacin hydrochloride (10 mg / L), and then stirred for 60 min in the dark to establish the adsorption-desorption equilibrium between the catalyst and the levofloxacin hydrochloride solution. A 500w xenon lamp was placed vertically 15 cm above the solution, 4 mL was sampled at regular intervals, and transferred to a centrifuge tube, and the photocatalyst was separated by centrifugation. Finally, the absorbance at 294 nm was measured using a UV-visible spectrophotometer, and the change in the concentration of levofloxacin hydrochloride was determined by the absorbance to analyze the degradation efficiency of the photocatalyst.

[0039] The experimental results are shown in Figure 6As shown in the figure, the mixed solution of catalyst and levofloxacin hydrochloride was placed under a 500w xenon lamp for irradiation. It can be clearly seen from the figure that the efficiency of pure BP in degrading levofloxacin hydrochloride is only 31.45%, while the composite material of Cu2O / BP is significantly higher than the two pure samples, and the degradation rate of Cu2O is only 10%. For the composite samples, the degradation rate of 1% Cu2O / BP is the lowest at 180min, which is only 65%; while the degradation effect of 3% and 4% Cu2O / BP is very effective, both reaching 89%; and the remaining 2%, 5%, and 10% Cu2O / BP have a relatively moderate degradation effect, which is basically maintained between 70% and 76%. In summary, it can be obtained that the degradation degree of the composite catalyst for antibiotics is still higher than that of the pure sample, and the best can increase the degradation efficiency by 2.83 times compared with BP.

[0040] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.

Claims

1. A Cu2O / black phosphorus catalyst for removing antibiotics from water, characterized in that: First, the BP nanolayer is synthesized, then the Cu2O particles are synthesized and finally loaded with BP. The Cu2O material is in the form of a spherical body, and the BP has a clear layered structure. The shape of the synthesized composite material is spherical nanoparticles embedded in the layered structure.

2. A method for preparing a Cu2O / black phosphorus catalyst for removing antibiotics in water, characterized in that: The following steps are involved: (1) Preparation of BP: black scale is prepared using red phosphorus; (2) Weigh Cu2O; (3) Preparation of Cu2O / BP: Cu2O and BP powders were dissolved in 80 mL EG, with 1 g of BP powder and a mass ratio of Cu2O to BP of 1%-10%. After stirring for 2 h, the mixture was transferred to an autoclave or a stainless steel autoclave, sealed and transferred to an oven, and then heated to 180 °C and maintained for 2 h. The final yellow product was filtered and washed with ethanol several times to remove unreacted EG, and dried in air at 40 °C.

3. The method for preparing the Cu2O / black phosphorus catalyst for removing antibiotics in water according to claim 2, characterized in that: The method for preparing BP is as follows: 0.25-0.75 g of red phosphorus powder is added with 70-80 mL of ethylenediamine, mixed evenly and then transferred to a polytetrafluoroethylene-lined stainless steel high-pressure reactor, placed in a constant temperature drying oven, heated at 165° C. for 24 hours, quickly cooled to room temperature, collected the product with cold water, centrifuged and washed with ethanol, and dried in a vacuum at 40° C.

4. The method for preparing the Cu2O / black phosphorus catalyst for removing antibiotics in water according to claim 3, characterized in that: After centrifugation, the cells were washed three times with ethanol.

5. The method for preparing the Cu2O / black phosphorus catalyst for removing antibiotics in water according to claim 2, characterized in that: The preparation method of Cu2O is as follows: 0.004 mol Cu(NO3)2·3H2O is dissolved in 70-90 mL EG, stirred for 2 h, transferred to an autoclave or a stainless steel autoclave, sealed and transferred to an oven, then heated to 180°C and maintained for 2 h, the final yellow product is filtered and washed with ethanol, and dried in air at 40°C.

6. The method for preparing the Cu2O / black phosphorus catalyst for removing antibiotics in water according to claim 5, characterized in that: Wash with ethanol three more times.

7. An application of Cu2O / black phosphorus catalyst for removing antibiotics from water, characterized in that: Application in photocatalytic degradation of levofloxacin hydrochloride wastewater.

8. The use of the Cu2O / black phosphorus catalyst for removing antibiotics in water according to claim 7, characterized in that: 3-5 mg of Cu2O / BP composite catalyst was added to 100 mL of 10 mg / L levofloxacin hydrochloride, and then stirred for 60 min in the dark to establish the adsorption-desorption equilibrium between the catalyst and the levofloxacin hydrochloride solution, and irradiated vertically with a xenon lamp.

9. The use of the Cu2O / black phosphorus catalyst for removing antibiotics in water according to claim 8, characterized in that: When irradiated by a xenon lamp, a magnetic stirrer is added to the levofloxacin hydrochloride solution containing a catalyst, and the solution is placed on a magnetic stirrer to continue stirring the reaction.

Citation Information

Patent Citations

  • Trititanium dicarbide / titanium dioxide / black phosphorus nanosheet composite photocatalyst, and preparation method and application thereof

    CN111185210A

  • Preparation method and application of nano Cu2O / wheat straw biochar photocatalyst

    CN117000242A

  • Large-scale hydrogen generation method through solar photocatalytic-photoelectrocatalytic decomposition of water

    WO2017128847A1

  • Black-phosphorus-modified copper-based catalyst and new use thereof in hydrogenation reduction reaction of organic matter

    WO2024045808A1